FAKTOR SOSIAL TERHADAP PENGELOLAAN RUANG TERBUKA HIJAU DI KAWASAN DESA RAWAN LONGSOR - shofwan, Moch. (WAHANA, 2017)
Green Open Space (RTH) is one of the balancing factors of an area in order to keep alignment to the dynamics of life around it. Social activity is part of the dynamics of society inbuilding and managing a region. Social activities can not be separated from the existing institutionsin the region, the institutional symbolized by the existence of groups (entities) that are capable ofproviding capacity for action on changes and policy making. Penanggungan village is a villagewhose territory is located on the slopes of the mountains, this village belongs to the category ofvillages prone to landslides. Social community of Penanggungan Village become the focus of studyrelated to Green Open Space management factor (RTH). The result of correlation analysis showsthat there is a relationship between social condition and Green Open Space (RTH) that is obtainedby significant value 0.000 which means less than 0.005 so that H0 result is rejected H1 accepted, itmeans there is relationship between variable X to Y. Based on result surveys in the field, most ofPenanggungan Village which has 4 hamlets namely Ngembes, Penanggungan, Sendang, andKemendung are entering the green area. This is in accordance with topographic conditions in thevillage Penanggungan into the topography that has an average height of 600-700 mdpl.